Semiotic Analysis of Smoking Prohibition Poster - Sri Ramadhani; Ratna Sari Dewi (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This study provided a semiotic analysis of smoking prohibition poster. This research was recommended for future researcher who want to do semiotic sign research. In addition, English Department students were advised to read this research to understand and increase their knowledge of semiotics. All semiotic signs were analyzed based on the type of semiotics proposed by Michael Kroeger for visual signs such as color, shape, line and Agus M. Hardjana for verbal signs, namely written text. The steps taken were to look carefully at the contents of the poster, clarify the contents of the poster and finally look for semiotic signs contained on the poster. The purpose of this research was to find out the types of semiotic signs contained in smoking prohibition poster. In this study using qualitative method. The source of this smoking prohibition poster was taken from the internet. In data collection, the posters were retrieved by searching through internet services as well as several other journal scientific works. In analyzing the data verbally and visually it consists of 3 data from 3 posters, 15 colors, 6 shapes, 5 lines and 11 written texts. Keyword: Verbal and Visual Sign, Smoking Prohibition Poster, Semiotic Analysis. Abstrak Penelitian ini memberikan analisis semiotika poster larangan merokok. Penelitian ini direkomendasikan untuk peneliti selanjutnya yang ingin melakukan penelitian tanda semiotik. Selain itu, mahasiswa Jurusan Bahasa Inggris disarankan untuk membaca penelitian ini untuk memahami dan menambah pengetahuan mereka tentang semiotika. Semua tanda semiotik dianalisis berdasarkan jenis semiotika yang dikemukakan oleh Michael Kroeger untuk tanda visual seperti warna, bentuk, garis dan Agus M. Hardjana untuk tanda verbal yaitu teks tertulis. Langkah-langkah yang dilakukan adalah mencermati isi poster, memperjelas isi poster dan terakhir mencari tanda-tanda semiotik yang terdapat pada poster. Tujuan dari penelitian ini adalah untuk mengetahui jenis-jenis tanda semiotika yang terdapat dalam poster larangan merokok. Dalam penelitian ini menggunakan metode kualitatif. Sumber poster larangan merokok ini diambil dari internet. Dalam pengumpulan data, poster diambil dengan mencari melalui layanan internet serta beberapa karya ilmiah jurnal lainnya. Dalam menganalisis data secara verbal dan visual terdiri dari 3 data dari 3 poster, 15 warna, 6 bentuk, 5 garis dan 11 teks tertulis. Kata Kunci: Tanda Verbal dan Visual, Poster Larangan Merokok, Analisis Semiotika